A study to assess the knowledge and competency of future medical practitioners regarding nutrition in health and disease - Ashwini S; Pushpa S. Patil (Al Ameen Medical College, 2023)
Background: Medical practitioners are a very credible source of information related to nutrition that decides an individual's health status. Hence, this study was conducted with an objective to assess the knowledge and competency of the future medical practitioners regarding nutrition in health and disease. Methods: This study was conducted among the interns of two batches. Interns answered a pre tested structured questionnaire containing multiple choice questions regarding knowledge related to nutrition. Based on the points scored in this, study participants were classified as high and low scorers. Among the high and low scoring interns, 10% were randomly selected. Their competency was assessed by Objective Structured Clinical Examination (OSCE) as they counselled simulated patients regarding nutrition in health and disease. Means and proportions were used to represent the descriptive data. Mann Whitney U test and Wilcoxon sign rank test were used to test the associations. Results: Mean knowledge score was 16.63 ± 2.43. As many as 176 (90.3%) were high scorers and 19 (9.7%) were low scorers. Mean competency score was 21.1 ± 4.7. Association between knowledge score (high and low scoring categories) and competency score (mean) was found statistically significant (Z = -2.67, p < 0.05). Conclusion: Though most of the interns were high scorers the mean knowledge as well as competency scores were still unsatisfactory. However, it was noted that knowledge and competency scores were associated showing that with better knowledge, competency also becomes better.